Evaluasi Strategi Penjualan Mobil Ditinjau Dari Faktor Sales Performance, Promosi, Dan Harga Di Dealer X Jakarta - Arif Dzulfikar; Firda Rahmahningsih; Dionisius Sundoro; Marison Sitorus; Gustiyan Taufik Mahardika (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Dealer X is a dealer located in Jakarta and operates in the sales, services, and spare parts sectors. Dealer X's sales data for 2024 has not met the sales target. Unfulfilled sales are caused by high sales employee turnover, promotional costs that are not commensurate with sales, and price competition and tight discounts. This study aims to find out whether there is a significant relationship between Sales Performance (X1), Price (X2), and Promotion (X3) to sales volume (Y1) and to develop the company's marketing strategy. The research approach used in this study is a quantitative approach through SEM-PLS analysis. The data used in this study are primary data through distributing questionnaires to car exhibition visitors. The sample used is a probability sampling type through random sampling technique with Slovin calculations. This study used a sample of 85 visitors. The results of the research analysis based on the t-statistic of 1.65 with a significant effect of p-value of 0.049 indicate that sales performance has an effect on sales volume. Based on the results of the promotion t-statistic of 2.740 and a significance level of p-value of 0.003, promotions have an effect on sales volume, and prices with a t-statistic of 5.145 with a significance level of p-value of 0.000, so prices have an effect on sales volume. Each indicator has a significant influence and has its own significance measure. New strategies that can be suggested for sales volume problems are to provide training and appreciation for each target achieved by sales consultants; test drive upgrades; provide bonuses in the form of free service and oil changes, free features such as dash cams and coatings; digital marketing with interesting content through social media; provide lower down payments.